Pengaruh Rasio Keuangan terhadap Harga Saham Perusahaan Sektor Transportasi yang terdaftar di Bursa Efek Indonesia Periode 2018-2020 - Arvin, Amanda Thalia; Sudradjat, Sudradjat; Arief, Khozin; Dahtiah, Neneng; Rufaedah, Yanti (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This research is aimed to find out how Financial Ratio measured by Current Ratio (CR), Debt to Equity Ratio (DER), Earning Per Share (EPS), dan Return on Equity (ROE) affects stock price of companies in transportation sector that listed in Indonesia Stock Exchange in period of 2018-2020. This research use Dated Panel Regression analysis with the population of 27 companies listed as transportation sector in IDX. Purposive sampling technique is used and generate 18 companies as samples. After the research process was done, it is known that EPS is the measure of financial ratio that have a significant effect on stcok prices.